Mentoring Technologies in Psychotherapy, Education, Management and Intercultural Relations: Results of the International Psychological Forum at the Russian-Armenian University - Asya S. Berberyan; Evgeniy B. Bashkin; Elene A. Bzhoyan; Dmitry S. Ermakov; Zhuldyz Amantay (Peoples' Friendship University of Russia (RUDN University), 2023)
On May 16-17, 2023, the Russian-Armenian University (RAU; Yerevan, Republic of Armenia) hosted the International Psychological Forum "The Phenomenon of Mentoring: an Existential-Humanistic Paradigm and Implementation Technologies in Education, Management, Psychotherapy and Intercultural Relations". The objectives of the Forum included (1) finding solutions to urgent problems of personal development through mentoring in the field of psychology, education, management, production, research, creative activities, etc.; (2) discussing scientific results and innovative technologies in the field of mentoring; (3) exchanging experience; and (4) establishing creative contacts. The forum brought together more than 100 participants (heads of scientific and educational organizations, scientific and pedagogical workers, practical psychologists, postgraduate and graduate students) from Armenia, Belarus, Germany, Kazakhstan, Kyrgyzstan, Russia, the Czech Republic, Israel, etc. The article presents the main events that included plenary and breakout sessions, roundtable discussions, interactive lectures, master classes, and a teleconference.